SEMANTIC FEATURES OF ASTRAL MYTHOLOGICAL UNITS IN ENGLISH AND KARAKALPAK - Usenova, V.J. (SCIENCE and SOCIETY, 2026)
This article examines the semantic features of astral mythological units based on definitional analysis within the framework of cognitive linguistics and linguocultural studies.
Keywords: astral mythological units; definitional analysis; mythological concept; linguocultural specificity; cognitive linguistics; lexical semantics